2016
DOI: 10.1371/journal.pcbi.1004811
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modelling Reveals ‘Hotspots’ on the Pathway to Enzyme-Substrate Complex Formation

Abstract: Dihydrodipicolinate synthase (DHDPS) catalyzes the first committed step in the diaminopimelate pathway of bacteria, yielding amino acids required for cell wall and protein biosyntheses. The essentiality of the enzyme to bacteria, coupled with its absence in humans, validates DHDPS as an antibacterial drug target. Conventional drug design efforts have thus far been unsuccessful in identifying potent DHDPS inhibitors. Here, we make use of contemporary molecular dynamics simulation and Markov state models to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Tyr107 interdigitates across the dimerisation interface between adjacent subunits to complete the catalytic triad (Dobson et al 2005). Arg138, located at the entrance to the active site cavity, plays a major role in binding the carboxyl group of (S)-ASA, as demonstrated by mutagenesis studies (Blickling et al 1997b;Dobson et al 2005), and also mediates entry of pyruvate into the active site as demonstrated by molecular dynamics simulations (Gordon et al 2016).…”
Section: Active Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Tyr107 interdigitates across the dimerisation interface between adjacent subunits to complete the catalytic triad (Dobson et al 2005). Arg138, located at the entrance to the active site cavity, plays a major role in binding the carboxyl group of (S)-ASA, as demonstrated by mutagenesis studies (Blickling et al 1997b;Dobson et al 2005), and also mediates entry of pyruvate into the active site as demonstrated by molecular dynamics simulations (Gordon et al 2016).…”
Section: Active Sitementioning
confidence: 99%
“…Pyruvate has been shown to stabilise the structure of DHDPS enzymes (Burgess et al 2008a;Gordon et al 2016;Voss et al 2010). For B. anthracis DHDPS, sedimentation equilibrium analyses demonstrated that the addition of pyruvate results in stabilisation of the tetrameric form with a 3-fold tighter tetramerisation dissociation constant compared to the apo enzyme (Voss et al 2010).…”
Section: Pyruvate Stabilisationmentioning
confidence: 99%
“…In another example, simulations of a calcium-binding calmodulin (CaM) domain showed binding-induced folding at higher calcium concentrations, while combined folding and induced fit occurred at lower calcium concentrations [ 223 ]. MD simulations of a homodimer dihydrodipicolinate synthase (DHDPS) revealed the role of the solvent-exposed Arg140 residue in the stabilization of the catalytic triad and binding of pyruvate as a substrate [ 224 ]. DHDPS simulations identified several metastable intermediates with favorable pyruvate interaction sites, and analyzed pyruvate binding pathways and kinetics, with researchers using MSM.…”
Section: Effect Of Small Molecule Interactions On Protein Structurmentioning
confidence: 99%
“…There is growing evidence that protein dynamics manifested through structural flexibility play a central role in the function of biological molecules. Often referred to as the fourth dimension of protein structure, the dynamic behavior of a polypeptide has been shown to contribute to the thermodynamic stability of func-tional states and also plays an important role in: (1) enzyme catalysis (Atkinson et al, 2013;Eisenmesser et al, 2005;Fraser et al, 2009;Gordon et al, 2016;Grossman et al, 2011;Henzler-Wildman and Kern, 2007); (2) ligand binding, which often involves the entry or exit of molecules into areas that would normally be occluded (Brunori et al, 2004;Gordon et al, 2016); and (3) allostery, where coupled structural fluctuations can transmit information between distant sites within the protein (Atkinson et al, 2013;Skovpen et al, 2016;Soares da Costa et al, 2016;Sowole et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dihydrodipicolinate synthase (DHDPS) is a homotetrameric enzyme with a molecular mass of $130 kDa that catalyzes the first committed step in the diaminopimelate (DAP) biosynthesis pathway of bacteria and plants (Figure 1A) (Atkinson et al, 2013;Blickling et al, 1997b;Dogovski et al, 2009Dogovski et al, , 2012Gordon et al, 2016;Skovpen et al, 2016;Soares da Costa et al, 2015Sowole et al, 2016;Yugari and Gilvarg, 1965). The DHDPS-catalyzed reaction involves the condensation of substrates, pyruvate and (S)-aspartate-b-semialdehyde (ASA), to form (4S)-hydroxy-2,3,4,5-tetrahydro-(2S)-dipicolinic acid (HTPA).…”
Section: Introductionmentioning
confidence: 99%